The Indicators of Library Service Quality and Satisfaction among Students of Nigerian Higher Education Institutions. A Principal Component Analysis Approach. - Ahmad, Muhammad Adamu; Saleh, Zafir BT. MD.; AbdulRazaq, Dr. Nurhanan Syafiah (IJRDO - Journal of Business Management, 2022)
The Provision and utilization of relevant library resources and services are fundamental for student satisfaction and institutional achievement. Employing the methodology of systematic review, we placed 41 English empirical articles on this subject into perspective. 21 library resources and service factors were relevant to determining student satisfaction in Nigerian Higher Education Institutions (HEIs). Principal Component Analysis (PCA) is a multivariate technique widely used for data reduction. This study further used the PCA to identify the relevant library resources and services variables with the highest variance. Arrangement of resources in their proper places on the shelves; library provides user education/orientation exercises (periodically); application of expert systems in reference service in: cataloging, classification, indexing, and acquisition; standby generators; and easily accessible resources (physical and electronic), which constituted the library’s mode of operation (process), were found to contribute 81.1% of the total variance. This indicates that these five factors were the top predictors of student satisfaction with academic libraries in Nigerian public tertiary institutions. The study can go a long way by providing tertiary institution librarians and libraries with a guide on formulating robust educational library policies. The policies, when developed, are expected to yield good results since the input of the policies originated from those the policies affect the most. Further studies can replicate this research in other developing countries to affirm or disprove the study results.